Abiotic Input of Fixed Nitrogen by Bolide Impacts to Gale Crater During the Hesperian: Insights From the Mars Science Laboratory. Issue 1 (15th January 2019) - Navarro‐González, Rafael; Navarro, Karina F.; Coll, Patrice; McKay, Christopher P.; Stern, Jennifer C.; Sutter, Brad; Archer, P. Douglas; Buch, Arnaud; Cabane, Michel; Conrad, Pamela G.; Eigenbrode, Jennifer L.; Franz, Heather B.; et al.
Abstract: Molecular hydrogen (H2 ) from volcanic emissions is suggested to warm the Martian surface when carbon dioxide (CO2 ) levels dropped from the Noachian (4100 to 3700 Myr) to the Hesperian (3700 to 3000 Myr). Its presence is expected to shift the conversion of molecular nitrogen (N2 ) into different forms of fixed nitrogen (N). Here we present experimental data and theoretical calculations that investigate the efficiency of nitrogen fixation by bolide impacts in CO2 ‐N2 atmospheres with or without H2 . Surprisingly, nitric oxide (NO) was produced more efficiently in 20% H2 in spite of being a reducing agent and not likely to increase the rate of nitrogen oxidation. Nevertheless, its presence led to a faster cooling of the shock wave raising the freeze‐out temperature of NO resulting in an enhanced yield. We estimate that the nitrogen fixation rate by bolide impacts varied from 7 × 10 −4 to 2 × 10 −3  g N·Myr −1 ·cm −2 and could imply fluvial concentration to explain the nitrogen (1.4 ± 0.7 g N·Myr −1 ·cm −2 ) detected as nitrite (NO2 − ) and nitrate (NO3 − ) by Curiosity at Yellowknife Bay. One possible explanation is that the nitrogen detected in the lacustrine sediments at Gale was deposited entirely on the crater's surface and was subsequently dissolved and transported by superficial and ground waters to the lake during favorable wet climatic conditions. The nitrogen content sharply decreases in younger sediments of the Murray formation suggesting a decline of H2 in the atmosphere and the rise of oxidizing conditions causing a shortage in the supply to putative microbial life. Plain Language Summary: Climate models are able to warm early Mars when CO2 sources were strong but fail at later times when liquid water still flowed on the surface. A possible solution for the climate puzzle is the presence of abundant H2 arising from volcanic emissions that could have kept the planet from freezing. H2 could have also played a key role in the chemistry of the atmosphere. Curiosity discovered the presence of nitrites and nitrates, forms of fixed nitrogen that are required for the origin and sustainability of life in sediments in Gale crater. Here we present theoretical and experimental data that quantify the conversion of molecular nitrogen into fixed nitrogen in the presence and absence of H2 by the entry shocks of asteroids in the Martian atmosphere and surface. Fixed nitrogen was originally deposited on the surface of Gale crater and then transported to the lake during favorable wet climatic conditions. We found that H2 is required to yield sufficient fixed nitrogen to explain its detection. The levels of fixed nitrogen sharply dropped in younger sediments suggesting a decline of H2 in the atmosphere and the rise of oxidizing conditions causing a nitrogen crisis to putative microbial communities. Key Points: A hydrogen‐rich atmosphere is required to explain the levels of fixed nitrogen that are found in sediments encountered in Gale crater Fixed nitrogen was deposited on the surface of the crater and then transported to the lake during favorable wet climatic conditions The levels of fixed nitrogen sharply decreased in younger sediments causing a shortage in the supply to putative microbial communities